ANALISIS PEMBELAJARAN JARAK JAUH DENGAN APLIKASI GOOGLE CLASSROOM - Raras Setyo Retno; Muhammad Seto Adjie Nugroho (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2023)
The purpose of this study is to analyze distance or online learning with the Google Classroom application in class 5B at SDN Jiwan 01 Madiun, academic year 2020/2021.The research method used is qualitative with a phenomenological approach. The data that the researcher obtained was then described into sentences. This research was conducted at SDN Jiwan 01 Madiun involving 20 students of class 5B as research subjects. Data collection was carried out by observing, interviewing sources and conducting documentation as reinforcement in research results. The data analysis used is data reduction, presenting data and drawing conclusions from the research results.The results of the study found that the use of the Google Classroom application could facilitate students' access to receive knowledge and learning from the teacher. Application as an effective and efficient learning media. Motivation and student learning outcomes increase because Google Classroom is actually used and structured to facilitate interaction between teachers and students as well as student guardians during online learning.